Pengaruh Model Pembelajaran Problem Based Learning dalam Meningkatkan Sikap Demokratis Mahasiswa - Daulat Nathanael Banjarnahor (PendIPA Journal of Science Education, 2021)
The purpose of this study was to describe: 1) How to implement civic education and learning to develop a democratic attitude and learning participation; 2) How to design a civic education learning model based on controversial issues in the mass media to develop a democratic attitude and student learning participation; 3) Based on the public To what extent can the civic education learning model of media controversial issues develop democratic attitudes and student participation in learning? It is indeed necessary to consider adopting appropriate learning methods to improve and discover students’ understanding of the knowledge conveyed by the teacher. Learning model Problem-based learning or problem-based learning is a student-oriented or student-centered learning model. Problem-based learning models have methods to deal with real-life problems, and this learning emphasizes problem-solving investigation activities. This research is a scientific paper. When using a problem-based learning learning model, a descriptive qualitative research method with a phenomenological description type is used to describe the learning process extensively and deeply. By paying attention to and analyzing the focus of reality or field experience that occurs on the research object. The object of the study is the students of HKBP Nommensen Pematangsiantar University, and the standard of study is the students participating in the civic education seminar.